A Para-Canalicular Abscess Resembling an Inflamed Chalazion - Diamantis Almaliotis; Elias Nakos; Thomas Siempis; Triantafyllia Koletsa; Ioannis Kostopoulos; Maria Chatzipantazi; Vasileios Karampatakis (Case Reports in Ophthalmological Medicine)
Background. Lacrimal infections by Actinomyces are rare and commonly misdiagnosed for long periods of time. They account for 2% of all lacrimal diseases. Case Report. We report a case of a 70-year-old female patient suffering from a para-canalicular abscess in the medial canthus of the left eye, beside the lower punctum lacrimale, resembling a chalazion. Purulence exited from the punctum lacrimale due to inflammation of the inferior canaliculus (canaliculitis). When pressure was applied to the mass, a second exit of purulence was also observed under the palpebral conjunctiva below the lacrimal caruncle. A surgical excision was performed followed by administration of local antibiotic therapy. The histopathological examination of the extracted mass revealed the existence of actinomycosis. Conclusion. Persistent or recurrent infections and lumps of the eyelids should be thoroughly investigated. Actinomyces as a causative agent should be considered. Differential diagnosis is broad and should include canaliculitis, chalazion, and multiple types of neoplasias. For this reason, in nonconclusive cases, a histopathological examination should be performed.